Efektivitas Pembelajaran Daring Pada Mata Pelajaran PPKn Dalam Meningkatkan Semangat Kebangsaan - Ady Martin Sinaga; Nur Lengkap Pandiangan; Reh Bungana Beru Perangin-angin (Journal Pendidikan Ilmu Pengetahuan Sosial, 2022)
This study aims to determine the level of effectiveness of online learning in Civics subjects in an effort to increase the spirit of nationalism for students as the nation's generation. This type of research uses descriptive research with a qualitative approach. Data collection techniques are carried out through literature studies and document studies. Online learning aims to meet educational standards by utilizing information technology by using computers or gadgets that are interconnected with students and teachers. The outbreak of the COVID-19 pandemic has forced all schools to carry out learning activities that are usually held face-to-face into online learning. Online learning also affects PPKn subjects but with interesting learning methods, the delivery of material will be effective for PPKn and have a positive effect on the national spirit of students facing life in the midst of the COVID-19 pandemic.